2018
DOI: 10.1111/bcpt.13088
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Screening of Six Protein Kinase Inhibitors for Time‐Dependent Inhibition of CYP2C8 and CYP3A4: Possible Implications with regard to Drug–Drug Interactions

Abstract: Several protein kinase inhibitors have been reported to affect cytochrome P450 (CYP) 3A by time-dependent inhibition. Herein, we tested a set of six kinase inhibitors for time-dependent inhibition of CYP2C8 and CYP3A4 in human liver microsomes. Dovitinib, midostaurin and nintedanib exhibited an increased inhibition of CYP3A4 after a 30-min. pre-incubation with NADPH, as compared to no pre-incubation (IC shift >1.5). Masitinib, trametinib and vatalanib did not affect CYP2C8 or CYP3A4 by time-dependent inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 63 publications
2
25
0
Order By: Relevance
“…Indeed, most of the TKI shown to induce RM in the first part of this review have been reported to cause CYP3A4 TDI, some of them also exhibiting a weak or moderate CYP2C8 TDI . The second part of the review thus summarizes the results of studies on CYP inactivation by TKI, especially when it is supported by evidence of RM formation in the presence of trapping agents.…”
Section: Tki and Cyp Enzymes: Evidence Of Tdimentioning
confidence: 93%
See 3 more Smart Citations
“…Indeed, most of the TKI shown to induce RM in the first part of this review have been reported to cause CYP3A4 TDI, some of them also exhibiting a weak or moderate CYP2C8 TDI . The second part of the review thus summarizes the results of studies on CYP inactivation by TKI, especially when it is supported by evidence of RM formation in the presence of trapping agents.…”
Section: Tki and Cyp Enzymes: Evidence Of Tdimentioning
confidence: 93%
“…Several studies have demonstrated that most TKI are prone to causing DDI since they are oral drugs prescribed over a long period of time to patients with comedications and because they are CYP inhibitors. TKI interfere with CYP by direct or reversible inhibition, but also by MBI . MBI arises from the bioactivation of drugs to RM, that have the propensity to permanently inactivate the enzyme involved in their generation by different mechanisms covalent binding to the heme porphyrin ring; co‐ordination (quasi‐irreversible binding) to the prosthetic heme iron to form a metabolite‐intermediate (MI) complex; covalent binding to the apoprotein, especially to key amino acids with nucleophilic side chains (arginine, cysteine, and lysine).…”
Section: Tki and Cyp Enzymes: Evidence Of Tdimentioning
confidence: 99%
See 2 more Smart Citations
“…Midostaurin is primarily metabolized by cytochrome P450 (CYP) 3A4 to two active metabolites: CGP62221 and CGP52421 . It exhibits time‐dependent pharmacokinetics and autoinduction, allowing peak concentrations during the first week of therapy, then decreasing to steady state by day 28 . Due to its metabolism, drug–drug interactions (DDI) are of concern.…”
Section: Drugs Approved By the Fda In 2017mentioning
confidence: 99%